2004
DOI: 10.1007/s00299-004-0799-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of vitamin E production in sunflower cell cultures

Abstract: The most biologically active component of vitamin E, alpha-tocopherol, is synthesized in its most effective stereoisomeric form only by photosynthetic organisms. Using sunflower cell cultures, a suitable in vitro production system of natural alpha-tocopherol was established. The most efficient medium was found to be MS basal medium with naphthaleneacetic acid and 6-benzylaminopurine with the addition of casaminoacids and myo-inositol. Culture feeding experiments using biosynthetic precursors showed that alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…Callus and cell suspension cultures were induced from plantlets where a-tocopherol was always more than 91% of the total tocopherols. It is interesting to note that such a percentage was maintained in cell cultures and the average a-tocopherol content was similar to that measured in the starting tissue (Table 2) [21,22]. Also callus cultures induced from safflower (Carthamus tinctorius) flower buds mainly accumulated a-tocopherol [23].…”
Section: Establishment Of In Vitro Cell Culturesmentioning
confidence: 71%
See 2 more Smart Citations
“…Callus and cell suspension cultures were induced from plantlets where a-tocopherol was always more than 91% of the total tocopherols. It is interesting to note that such a percentage was maintained in cell cultures and the average a-tocopherol content was similar to that measured in the starting tissue (Table 2) [21,22]. Also callus cultures induced from safflower (Carthamus tinctorius) flower buds mainly accumulated a-tocopherol [23].…”
Section: Establishment Of In Vitro Cell Culturesmentioning
confidence: 71%
“…The most efficient medium was found to be MS basal medium containing naphthaleneacetic acid and 6-benzylaminopurine with the addition of casaminoacids and myo-inositol. Furthermore, a 78% increase of a-tocopherol in cell suspensions in the stationary phase was obtained by selecting cells for longer subculture intervals, probably due to the response to a stress condition (Table 2) [22]. The ability of casaminoacids and myo-inositol to enhance tocopherol production had already been observed in safflower cell cultures [23].…”
Section: Establishment Of In Vitro Cell Culturesmentioning
confidence: 94%
See 1 more Smart Citation
“…These data indicate that the availability of both tocopherol precursors restricts vitamin E biosynthesis, with phytol being the most limiting. In contrast, in sunflower suspension cells, HGA feeding stimulated tocopherol accumulation ($30%), while phytol supplementation had no effect [40]. Finally, in soybean suspension cultures, tocopherol content increased twofold in response to either HGA or phytol feeding, and fivefold when both precursors were added simultaneously [15].…”
Section: Tocochromanolmentioning
confidence: 95%
“…Activity (IU/mg) Activity (%) In order to identify the biosynthetic steps limiting tocochromanol accumulation in plants, tocopherol production was investigated in cell cultures fed with metabolic intermediates [15,39,40]. While these studies concluded that both HGA and phytol had the greatest effects on vitamin E biosynthesis, their conclusions differ on which compound is the most limiting.…”
Section: Tocochromanolmentioning
confidence: 99%